Extraction of oil from passion fruit seeds using surfactant-assisted aqueous extraction - Surlehan, H. F.; Noor Azman, N. A.; Zakaria, R. A.; Mohd Amin, N. A. (Rynnye Lyan Resources, 2019)
Passion fruit (Passiflora edulis) has a distinctive aroma and flavour and is widely commercialized as fruit juice. A high amount of seeds waste is produced during the juice production. The seeds contain high amounts of oil which can be extracted by hexane or pressing. However, hexane is a hazardous chemical, while pressing generally results in low yield of oil. In this study, surfactant-assisted aqueous extraction (SAAE) was explored to extract the oil at room temperature (25˚C) from the seeds by combining Tween 20 and Span 20 food-grade surfactants. It was determined that Hydrophilic-Lipophilic Balance (HLB 14 to 16) resulted in the lowest interfacial tension (IFT) between the oil and the surfactant solution. The extraction yield was found to correlate well with the interfacial tension whereby reduction in IFT causes an increase in the extraction yield. The highest extraction (80%) was found at 1% surfactant concentration which is at the critical micelle concentration (CMC) of the surfactant solution. The optimum parameter for extraction was 1:19 solid-liquid ratio, 15 mins extraction at 25°C. SAAE with food-grade surfactant can be a simple and viable technique to extract the waste passion fruit seed at low temperature, short time and low surfactant usage. The oil was found to contain phenols (26.3 mg GAE/g), squalene (0.65 mg/g), β-sitosterol (0.58 mg/g) and vitamin E (0.1 mg/g). The main free fatty acids present were linoleic (65.72%), oleic (17.9%) and palmitic (11.41%).